درجة تضمين مفاهيم وتطبيقات الذكاء الاصطناعي في محتوى مناهج الرياضيات بمرحلة التعليم الأساسي بسلطنة عمان - الشيدي، خالد بن جمعة بن خميس; السعيدي، حميد بن مسلم بن سعيد (جامعة فلسطين التقنية خضوري - عمادة البحث العلمي, 2022)
هدفت الدراسة إلى التعرف على درجة تضمين مفاهيم وتطبيقات الذكاء الاصطناعي في محتوى مناهج الرياضيات في مدارس التعليم الأساسي بسلطنة عمان، ولتحقيق أهداف الدراسة استخدم الباحثان المنهج الوصفي الكمي، وذلك بإعداد بطاقة تحليل مكونة من (24) عبارة موزعة على خمس مجالات وبعد التحقق من صدق الأداة وثباتها، تم تطبيقها على مناهج الرياضيات للصفين السابع والثامن للتعليم الأساسي. وقد كشفت نتائج الدراسة أن درجة تضمين مفاهيم وتطبيقات الذكاء الاصطناعي في محتوى مناهج الرياضيات للصفين السابع والثامن بسلطنة عمان جاءت بدرجة ضعيفة، حيث بلغت في محتوى كتاب الطالب للفصل الأول (3.50%)، وكتاب الطالب للفصل الثاني (0.70%)، وكتاب النشاط للفصل الأول (1.70%)، في حين جاء كتاب النشاط للفصل الثاني (2.40%). كما أشارت النتائج إلى أن درجة تضمين مفاهيم وتطبيقات الذكاء الاصطناعي في محتوى مناهج الرياضيات للصف الثامن بسلطنة عمان جاءت أيضا بدرجة ضعيفة، حيث بلغت في محتوى كتاب الطالب للفصل الأول (0.70%)، وكتاب الطالب للفصل الثاني (8.80%)، وكتاب النشاط للفصل الأول (2%)، في حين جاء كتاب النشاط للفصل الثاني (0.30%). وأوصى الباحثان بضرورة تضمين مفاهيم وبرمجيات الذكاء الاصطناعي في مناهج الرياضيات، وتدريب معلمي الرياضيات على تدريس مفاهيم وتطبيقات الذكاء الاصطناعي، واستبدال موضوعات الأرقام الرومانية بالمفاهيم الرقمية الحديثة للذكاء الاصطناعي. The study aimed to identify the degree of inclusion of artificial intelligence concepts and applications in the content of mathematics curricula in basic education schools in the Sultanate of Oman. The quantitative descriptive approach was used. A questionnaire tool of 24 items was prepared, checked for reliability and validity, and used for Mathematics content analysis. The study was applied for the seventh and eighth grades of basic education. The results of the study revealed that the degree of inclusion of artificial intelligence concepts and applications in the content of mathematics curricula for the seventh and eighth grades in the Sultanate of Oman was weak, as it reached 3.50% in the content of the student’s book for the first semester, the student’s book for the second semester (0.70%), and the activity book for the first semester. (1.70%), while the activity book for the second semester came in (2.40%). The results also indicated that the degree of inclusion of artificial intelligence concepts and applications in the content of mathematics curricula for the eighth grade in the Sultanate of Oman was also weak, as it reached in the content of the student’s book for the first semester (0.70%), the student’s book for the second semester (8.80%), and the activity book for the first semester (2%), while the activity book came for the second semester (0.30%). The researchers recommended the necessity of including artificial intelligence concepts and software in mathematics curricula, training mathematics teachers to teach concepts and applications of artificial intelligence, and replacing Roman numeral topics with modern digital concepts of artificial intelligence.
Keywords: الثورة الصناعية الرابعة -- صعوبات التعلم -- معلمو الرياضيات -- سلطنة عمان